Assessing the influence of wheelchair technology on perception of participation in spinal cord injury - Chaves, Eliana S.; Boninger, Michael L.; Cooper, Rosemarie; Fitzgerald, Shirley G.; Gray, David B.; Cooper, Rory A. (Archives of physical medicine and rehabilitation, 2004)
Chaves ES, Boninger ML, Cooper R, Fitzgerald SG, Gray DB, Cooper RA. Assessing the influence of wheelchair technology on perception of participation in spinal cord injury. Arch Phys Med Rehabil 2004;85:1854-8. To investigate factors related to the wheelchair, impairment, and environment that affect perception of participation of persons with spinal cord injury (SCI) in activities performed in 3 settings: in the home, in the community, and during transportation. Cross-sectional study. Research centers and a specialized assistive technology (AT) clinic in Pittsburgh (Pitt). Research centers and community-based rehabilitation technology suppliers in Saint Louis (SL). Seventy wheelchair users with SCI. Subjects from Pitt and SL completed a written survey of AT usage in daily activities. Subjects were asked 5 questions within each setting (home, community, transportation) related to their perceived reason for functional limitations. The wheelchair was the most commonly cited factor limiting participation, followed by physical impairment and physical environment. Twenty-one percent of subjects with paraplegia reported pain as a limiting factor for their transportation use, significantly more ( P=.047) than subjects with tetraplegia (3%). A trend ( P=.099) was seen toward a higher percentage of subjects with tetraplegia (tetraplegia, 7%; paraplegia, 3%) reporting lack of equipment as a limiting factor for use of transportation. Differences were also seen across sites. The wheelchair was the most commonly cited limiting factor, followed by physical impairment and physical environment. The wheelchair is the most important mobility device used by persons with SCI and the one that users most associate with barriers.